The Students’ Accuracy in Translating Positive Politeness Markers in English Department of Universitas Negeri Padang - Rizky Anggia; Havid Ardi (Universitas Negeri Padang, 2021)
This research was aimed to find out the students’accuracy in translating positive politeness markers in the novel “Dilan 1990” at third year students of English Department of Universitas Negeri Padang. The subject of this research was the third year students of English department of Universitas Negeri Padang. The focus is the students’ accuracy in translating positive politeness markers. This research is qualitative descriptive study. Out of 60 students, 35% of them were chosen to be the sample by using cluster random sampling. The data were collected by using test. The results of this research show the students’ accuracy was (76%). Related to the result found, the students’ accuracy in translating positive politeness markers was good. The difficulty in translation cannot be seen from the type of strategy used only, but also many aspects affect the result of students’ translation. Based on the research that the author did, students need to know about the context and situation appear in each utterance. The most commonly problems that the students did in their translation process is they did not pay attention to the whole context. There were also some changes in the strategy used in politeness. It is shown by the utterances strategy change in their translation product. The understanding politeness strategy gives an advantage for the students in producing accurate translation product.